Machine translation and audiovisual products: a case study - Adrià Martín-Mor; Pilar Sánchez-Gijón (JoSTrans: The Journal of Specialised Translation)
Much has been said and written about the effects that machine translation (MT) is having on all kinds of published products. This paper discusses the introduction of MT in the localisation of audiovisual products in general and particularly voiceover documentaries. Incorporating MT into the translation of voiceover documentaries would boost the dissemination of non-commercial or minority products, and could enhance the spread of culture. While it might at first seem that MT could be easily integrated into translation for documentaries, some particular aspects make it difficult to use MT to translate for dubbing or for voice-overs. We therefore designed an exploratory study using a corpus containing different texts of a film, in order to compare the results of different automatic measures. The preliminary results show that different results are obtained for different types of speech and that the application of automatic metrics produces similar results. In this article, we will present furthermore the methodological design, which might be considered useful for other studies of this kind1.